Working fathers : new strategies for balancing home and family - Levine, James A. (Harcourt Brace & Company San DiegoUS, 1998)
Examines the dilemma which working fathers face as they try to balance their commitment to family, and to work. Includes strategies for improving thier relationships with their children and wives; and suggests ways to create a father-friendly workplace.